When creation is sacred: restoring the indigenous Jesus - Taber-Hamilton, Rachel K. (Anglican theological review, 2021)
This article argues that the dominant culture perception of indigenous peoples remains intimately woven with dominant culture beliefs about the environment. Taber-Hamilton asserts that if the environment is viewed as expendable within a model of colonial consumerism, then indigenous peoples who inhabit colonized spaces are viewed as expendable, as part of the cooptation and exploitation of environmental resources. Taber-Hamilton provides case examples that emphasize the critical need for establishing collaborative partnerships with indigenous communities for effective environmental justice advocacy. Providing a perspective of Christian theology through the lens of the indigenous environmental context, Taber-Hamilton concludes with advances in relationships between the Episcopal Church and indigenous peoples. She advocates that effective relationships with indigenous communities require a decolonized Christian faith that restores the indigenous Jesus to the landscape of theological reflection, a restoration that benefits both faith-based environmental advocacy and the Church’s relationship with indigenous peoples.